2021
DOI: 10.13057/biodiv/d220742
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: New report of Aedes albopictus in Souk Ahras, Northeast Algeria

Abstract: Abstract. Hamaidia K, Soltani N. 2021. Short communication: New report of Aedes albopictus in Souk Ahras, Northeast Algeria. Biodiversitas 22: 2901-2906. The present paper reports the occurrence of Aedes albopictus (Skuse), an aggressive Asian tiger mosquito in the city of Souk-Ahras (Northeast of Algeria). A “26 April” estate’ inhabitants (Souk-Ahras province) have reported unusual daytime bites by a striped mosquito. On early September 2020, an intensive field inspection was carried out for potential mosquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…In this study, we concluded that C. longiareolata is the most abundant species in the region of El Kantara (89.91%) and is a widely distributed species in the Mediterranean region (Brunhes et al, 2001). Studies indicate its existence in polluted sites and permanent sites of stagnant water with rich or poor vegetation in the regions of Tébessa and Souk Ahras (Hamaidia, 2004). The same results were found by Belkhiri et al (2021) in the Batna region.…”
Section: Genressupporting
confidence: 68%
“…In this study, we concluded that C. longiareolata is the most abundant species in the region of El Kantara (89.91%) and is a widely distributed species in the Mediterranean region (Brunhes et al, 2001). Studies indicate its existence in polluted sites and permanent sites of stagnant water with rich or poor vegetation in the regions of Tébessa and Souk Ahras (Hamaidia, 2004). The same results were found by Belkhiri et al (2021) in the Batna region.…”
Section: Genressupporting
confidence: 68%
“…Despite decades of effective managing efforts using chemical insecticides as the best way to reduce adult mosquito's populations, vector‐borne disease transmission persists (Ferraguti et al, 2021). To detect their occurrence and spatiotemporal distribution, updated inventories of mosquito larvae (Diptera: Culicidae) in Northeastern Algeria were carried out to perform an effective control program (Benmalek et al, 2018; Bouabida et al, 2012; Hafsi et al, 2021; Hamaidia et al, 2016; Hamaidia & Berchi, 2018; Hamaidia & Soltani, 2021). These surveys would be needed to assess the risk of invasive vector species emergence (Benallal et al, 2019; Hamaidia & Soltani, 2021; Lafri et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Zerguine et al 2018 collected 7,615 specimens belonging to 75 species in four subfamilies of the Chironomidae fauna in the Oued Charef basin, northeastern Algeria. Hamaidia and Berchi (2018) studied the Culicidae of northeastern Algeria in the region of Souk-ahras and revealed the presence of 14 species belonging to the two subfamilies (Culicinae and Anophelinae). The study of beetles populating the continental waters of Algeria has been carried out by some researchers: Lamine et al (2019); 51 beetles divided into 2 sub-orders, 34 genera, and 10 families have been identified.…”
Section: Inventory and Systematic Study Of The Invertebrate Faunamentioning
confidence: 99%
“…The study on the biodiversity of freshwater invertebrates, both running and stagnant, includes the systematic determination of insects, crustaceans, and mollusks. Recent studies have been made in several aquatic ecosystems in Northeast Algeria, like on the aquatic beetle community living in Tonga Lake (Mahmoudi et al 2022), morphometry and reproduction of a crustacean species Atyaephyra desmaresti Millet 1831 used as a bioindicator species of health quality of hydrosystems (Ameur et al 2022), or on culicidian fauna in some habitats from Souk-Ahras province (Hafsi et al 2021;Hamaidia and Soltani 2021). These studies show the importance of ecological factors in the distribution of species.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation